The Lotterys plus one - Donoghue, Emma, 1969-; Hadilaksono, Caroline (New York, NY : Arthur A. Levine Books, an imprint of Scholastic Inc., 2017)
Once upon a time, two couples with Jamaican, Mohawk, Indian, and Scottish ethnic roots won the lottery and bought a big house where all of them, four adults and seven adopted and biological children, could live together in harmony--but change is inevitable, especially when a disagreeable grandfather comes to stay.
Keywords: Families -- Ontario -- Toronto -- Juvenile fiction; Siblings -- Juvenile fiction; Grandfathers -- Juvenile fiction; Toronto (Ont.) -- Juvenile fiction; Illustrated children's books; Family life -- Fiction; Brothers and sisters -- Fiction; Grandfathers -- Fiction; Toronto (Ont.) -- Fiction; Canada -- Fiction; Families -- Ontario -- Toronto -- Fiction; Family life -- Fiction; Brothers and sisters -- Fiction; Grandfathers -- Fiction; Toronto (Ont) -- Fiction; Canada -- Fiction